Hubungan Kebiasaan Sarapan Dan Status Gizi Dengan Prestasi Belajar Siswa SDN 345 Kaduaja Benteng Deata Kecamatan Gandang Batu Sillanan, Kabupaten Tana Toraja - Hayuti Windha Pagiu; Nofita Tudang Rombeallo; Fera Dwiyanti; Nurul Zahira A.N (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Introduction: Children's growth and development and learning achievements require adequate nutritional intake by eating breakfast or what is usually called breakfast. Research objective: To determine the relationship between breakfast habits and nutritional status with student learning achievement at SDN 345 ​​Kaduaja, Benteng Deata, Gandang Batu Sillanan District, Tana Toraja Regency. Research method: This research method is descriptive correlational with a cross sectional approach, the sample size is 37 respondents. represents the population. This sampling technique is Proportional Stratified Random Sampling. Data was collected using a questionnaire and tested statistically. Research results: From the results of this research, the majority of respondents were female, 21 students (56.8%), the majority of respondents were 10 years old, 12 students (32.4%). The majority of respondents with good breakfast habits were 19 students (51.4%), the majority of respondents with good nutritional status were 19 students (51.4%) and the majority of respondents with good performance were 25 students (67.6%). The results of the Fisher's exact test statistical test showed that there was no relationship between breakfast habits and learning achievement with a p-value = 0.528 and it was found that there was a relationship between nutritional status and learning achievement with a p-value = 0.033. Conclusion: Based on the research results, it was concluded that there was no relationship breakfast habits and learning achievement. There is a relationship between nutritional status and learning achievement of students at SDN 345 ​​Kaduaja, Deata Deata Castle, Gandang Batu Sillanan subdistrict, Tana Toraja Regency. It is recommended that students meet their nutritional needs by eating healthy and balanced foods.